THE EFFECT OF TAX COLLECTION EFFECTIVENESS AND THE USE OF TAPPING BOXES ON RESTAURANT TAXPAYER COMPLIANCE IN PADANG CITY - Fauziati, Popi; Husna, Nailal; Rahmi, Siti; Desda, Mia Muchia; Morelent, Yetty; Azzahra, Alia Rahma (Institut Teknologi dan Bisnis Asia Malang, 2024)
This study aims to determine the effect of the effectiveness of tax collection and the use of tapping boxes on taxpayer compliance of restaurant taxpayers in Padang City. This research is a type of quanlitative research with a descriptive approach. The population and sample in this study are restaurants in the city of Padang. The sampling method uses the slovin formula, with a total sample of 67. The data used in this study is primary data collected through questionnaires to restaurant owners according to data from the Central Bureau of Statistics (BPS) of Padang City. Then the collected data was tested with multiple linear regression analysis R2 test, F test, t test. The results showed that the variable effectiveness of tax collection had an effect on restaurant taxpayer compliance in the city of Padang and the variable use of tapping boxes also had an effect on taxpayer compliance in the city of Padang.